(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aimed to compare the results of emergency and elective cholecystectomy in patients admitted due to acute biliary pancreatitis.Material and Methods: A total of 632 patients admitted due to acute biliary pancreatitis were retrospectively evalauted. Patients with Ranson ≥ 3 and hour 48 CRP > 15 were considered as severe pancreatitis and excluded from the study. Patients were divided into two groups. Group 1 consisted of the patients who underwent emergency cholecystectomy after 48 hours, while Group 2 included the patients who underwent interval cholecystectomy. Results: A total of 386 patients were enrolled in the study. Group 1 consisted of 214 patients. The mean Ranson score was found as 1.3±0.9 in Group 1 and 0.92±0.7 in Group 2. A total of 148 patients in Group 1 and 117 patients in Group 2 had comorbidity (p=0.81). Conversion was performed in 8 patients in Group 1 and 5 patients in Group 2 (p = 0.78). Bile duct injury was not detected in either group. Among the patients in the interval cholecystectomy group, 7 patients were admitted to the hospital due to acute pancreatitits and total 13 patients due to biliopancreatic reasons during the interval period. Conclusion: No effect of cholecystectomy timing was detected on the conversion rates and development of complications. However, development of recurrence and related complications in the waiting period of the patients could be prevented by performing early cholecystectomy.